LIBERTARIAN PREMISES OF KNOWLEDGE COMMERCIALIZATION IN HIGHER EDUCATION INSTITUTIONS - Robert CIBOROWSKI; Karolina TRZASKA; Marian ZALESKO (Humanities and Social Sciences)
Academic freedom is part of the multi-faceted discourse on liberty. Enabling universities to fulfill their core mission of advancing knowledge is a fundamental element of pursuing academic freedom. The purpose of this article is to analyze the issue of academic freedom, including the conditions and processes involved in conducting research and accomplishing the objectives of higher education. Key factors in the process of knowledge production and commercialization include historical background, perception of independence paradigms, adopted university management models, and the size and structure of funding. Among the crucial premises for the commercialization of knowledge in higher education are the sense of community within the academic environment and accumulated past funding (related to the "Matthew Effect").